SAT0374 The euromyositis registry: an international description of myositis. (15th June 2017) - Lilleker, JB; Vencovsky, J; Wang, G; Wedderburn, LR; Diederichsen, LP; Schmidt, J; Jordan, P; Benveniste, O; Danieli, MG; Dankό, K; Thuy, NTP; Mercado, M Vazquez-Del; et al.
Abstract : Background: The idiopathic inflammatory myopathies (IIM) represent a rare and heterogeneous group of multisystem autoimmune diseases. The rarity of IIM has hampered research efforts, resulting in remarkably limited therapeutic evidence. The EuroMyositis Registry was created to pool resources and expertise across the international IIM research community. Objectives: To describe the phenotypic characteristics of different IIM subtypes. Associations with malignancy, interstitial lung disease (ILD), cardiac involvement and dysphagia were assessed. Methods: Pooled data from the EuroMyositis Registry (from Belgium, China, Czech Republic, Hungary, Italy, Mexico, Norway, Sweden, Switzerland, UK, Vietnam) were obtained. Associations were assessed using logistic regression and multinomial logistic regression with polymyositis (PM) as the reference group. Results: Data regarding 3, 196 patients were analysed. The UK was the largest contributor (n=1, 307). The most common diagnoses were dermatomyositis (34%), PM (32%) and connective tissue disease (CTD)-overlap myositis (15%). In those with anti-synthetase syndrome (7%), 85% had muscle weakness, 86% ILD and 58% arthritis. Overall, 43% had a myositis specific antibody, most commonly anti-Jo1 autoantibodies (20%). Glucocorticoid usage was noted in 98%. Most commonly used disease modifying agents were methotrexate (71%) and azathioprine (50%). Malignancy occurred in 9% and was associated with a diagnosis of dermatomyositis (Relative Risk Ratio [RRR] 1.68, 95% CI 1.09–2.56, p=0.018). Cardiac involvement occurred in 9%, most commonly in those with CTD-overlap myositis (13%), and was associated with a higher Health Assessment Questionnaire disability index (1 versus 0.75, OR 1.40, 95% CI 1.03–1.91, p=0.031). Dysphagia occurred in 39% and was associated with a diagnosis of CTD-overlap myositis (RRR 2.25, 95% CI 1.61–3.15, p<0.001). Conclusions: This large international cohort demonstrates the heterogeneity of IIM and the burden of associated malignancy, ILD, cardiac and gastrointestinal involvement. The EuroMyositis Registry facilitates international collaborative research outputs, underlining the benefits of harmonised data collection methodology between centres. Acknowledgements: This work was supported by researchers at the National Institute for Health Research (NIHR) Biomedical Research Unit. The views expressed are those of the authors and not necessarily those of the UK National Health Service, the NIHR or the UK Department of Health Disclosure of Interest: J. Lilleker: None declared, J. Vencovsky: None declared, G. Wang: None declared, L. Wedderburn Grant/research support from: The UK JDM Cohort and Biomarker study is supported by grants from the NIHR and Myositis UK, L. Diederichsen: None declared, J. Schmidt: None declared, P. Jordan: None declared, O. Benveniste: None declared, M. G. Danieli: None declared, K. Dankό: None declared, N. T. P. Thuy: None declared, M. Vazquez-Del Mercado: None declared, Ø. Molberg: None declared, B. De Paepe: None declared, J. De Bleecker: None declared, B. Maurer Grant/research support from: AbbVie, Protagen, EMDO, Novartis, Roche, Actelion, N. Pipitone Speakers bureau: GRAPPA Workshop, Alfa-Wassermann, N. McHugh: None declared, Z. Betteridge: None declared, P. New: None declared, R. Cooper: None declared, W. Ollier: None declared, J. Lamb Grant/research support from: MedImmune, N. S. Krogh: None declared, I. Lundberg Grant/research support from: Astra-Zeneca, Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Idera, H. Chinoy Grant/research support from: MedImmune, Novartis